Promotion of healthy behaviours: insights from social marketing research and practice to promote health behavior change - Bastos, Adriana de Fatima Valente (2019)
This thesis, structured as a set of three articles, has the goal of examining the promotion of a healthy lifestyle through the lens of social marketing. Article 1 is a conceptual study, which discusses why social marketing should incorporate the Behaviour Change Wheel model in its toolkit. Article 2 is a case-based study, which describes a population-based intervention that was undertaken to foster the practice of physical activity and healthy eating in an entire Brazilian city, while Article 3 is an empirical application of the stage of change from the Transtheoretical model and addresses the motivation for maintaining healthy habits over time. Social marketing permeates all three studies, since Article 1 offers a synthesis of the main models used in social marketing and Articles 2 and 3 show applied examples of a health intervention aimed at changing behaviour, which is the main goal of social marketing.